2008
DOI: 10.1097/gim.0b013e3181634867
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, sex, and the incidence of congenital heart defects: a report from the National Down Syndrome Project

Abstract: Purpose: The population-based National Down Syndrome Project combined epidemiological and molecular methods to study congenital heart defects in Down syndrome. Methods: Between 2000 and 2004, six sites collected DNA, clinical, and epidemiological information on parents and infants. We used logistic regression to examine factors associated with the most common Down syndrome-associated heart defects. Results: Of 1469 eligible infants, major cardiac defects were present in 44%; atrioventricular septal defect (39%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
212
6
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(262 citation statements)
references
References 32 publications
19
212
6
15
Order By: Relevance
“…In this study, we found similar results, and heart diseases most frequently encountered were AVSD and VSD. The incidence of girls with heart disease (58.3%) was slightly higher compared to boys as it is described in the literature on population samples with DS [21].…”
Section: Discussionmentioning
confidence: 63%
“…In this study, we found similar results, and heart diseases most frequently encountered were AVSD and VSD. The incidence of girls with heart disease (58.3%) was slightly higher compared to boys as it is described in the literature on population samples with DS [21].…”
Section: Discussionmentioning
confidence: 63%
“…Divers trends have been reported. AVSD was the main congenital heart disease of the child with Down syndrome in American, Turkish and Swedish studies [16][17][18][19]. In a recent publication with the description of CHDs among Swedish live born infants with DS from 1992 to 2012, the rate of AVSD decreased from 46% to 30%, whereas the rate of ventricular septal defect had doubled from 14% to 31% [20].…”
Section: Discussionmentioning
confidence: 99%
“…Es ampliamente conocido que el 40 a 60% de las personas con SD tienen CC 12 , en nuestra serie, las CC afectaron a cerca del 60%, frecuencia mayor a lo reportado en la literatura internacional 13,14 , debido probablemente a que nuestra institución es también un centro de referencia de cardiocirugía pediátrica. Al igual que lo reportado en la literatura, los tipos de CC predominantes fueron los defectos septales aurículo ventriculares [12][13][14][15] .…”
Section: Discussionunclassified
“…Al igual que lo reportado en la literatura, los tipos de CC predominantes fueron los defectos septales aurículo ventriculares [12][13][14][15] . En la etapa de la adolescencia cobra importancia no tan sólo el seguimiento de aquellos pacientes que requirieron cirugía (que alcanzó a la mitad de los que tuvieron CC), si no que se debiera estar atento a la aparición de soplos y desarrollo de valvulopatías.…”
Section: Discussionunclassified